TINDAK PIDANA PEMERASAN DAN PENGANCAMAN MELALUI MEDIA SOSIAL (STUDI PUTUSAN PENGADILAN NEGERI MATARAM NOMOR 272/PID.SUS/2019/PN.MTR) - Endri Susanto; Lalu Parman; Ufran Ufran (LPPM Universitas Ekasakti Padang, 2023)
This research is a normative legal research that aims to analyze the concept of the crime of extortion and threats through social media in the formulation of Article 27 paragraph (4) of the ITE Law and to analyze the considerations of judges in acquitting decisions (vrijspraak) against cases of criminal acts of extortion and threats through social media in Mataram District Court Decision No. 272/Pid.Sus/2019/PN.Mtr. The results of the research are analyzed that the previous offense of extortion and threats (afpersing en afdreiging) in the Criminal Code were two different crimes, but the ITE Law formulates the crime of extortion and threats in one formulation of the Article. Extortion and threats carried out through electronic media use the element of extortion as the first element because extortion is the substance, while threats are a method used by perpetrators to carry out acts of extortion. In the acquittal (vrijspraak) against the criminal act of extortion and threats through social media in the Mataram District Court Decision Number 272/Pid.Sus/2019/Pn.Mtr that at the trial the Defendant explained the intent and purpose of the Defendant in providing comments on Social Media was so that funds Earthquake assistance was quickly realized by the Regional Government of Kab. North Lombok, Another consideration is that based on proven legal facts, the defendant's posting on his Facebook account was not motivated by extortion and the defendant did not get any benefit, therefore the element of extortion and/or threats was not proven.